1992
DOI: 10.1001/archsurg.1992.01420010037006
|View full text |Cite
|
Sign up to set email alerts
|

Liver Nonparenchymal Cells Are Stimulated to Provide Interleukin 6 for Induction of the Hepatic Acute-Phase Response in Endotoxemia but Not in Remote Localized Inflammation

Abstract: It has been postulated that Kupffer cells provide signals that regulate hepatocyte responses in sepsis and inflammation. Although in vitro data support such a hypothesis, to our knowledge, no in vivo evidence has been reported. We injected rats with lipopolysaccharide intraperitoneally to simulate sepsis or turpentine intramuscularly to mimic localized inflammation. Both treatments are known to induce the hepatic acute-phase response. Liver nonparenchymal cells and hepatocytes were isolated and placed in cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 31 publications
5
17
0
2
Order By: Relevance
“…Several cell types, particularly myeloid cells, are known to produce IL-1b and IL-6 in response to LPS. For example, it was reported that liver Küpfer cells are stimulated to provide the IL-6 signal to hepatocytes during endotoxemia (40). Consistent with these different observations, we observed elevated levels of IL-1b and IL-6 in the circulation and liver of LPS-treated mice (data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…Several cell types, particularly myeloid cells, are known to produce IL-1b and IL-6 in response to LPS. For example, it was reported that liver Küpfer cells are stimulated to provide the IL-6 signal to hepatocytes during endotoxemia (40). Consistent with these different observations, we observed elevated levels of IL-1b and IL-6 in the circulation and liver of LPS-treated mice (data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…However, there is increasing evidence that the intestinal mucosa responds to endotoxin in a manner similar to the well characterized hepatic acute phase response (Molmenti et al, 1993;Wang et al, 1998). Endotoxin is known to stimulate the production of IL-6 in liver (Billiar et al, 1992). Indeed, we observed an increased expression of IL-6 mRNA in the intestinal segments of LPS-treated rats that is consistent with that reported by Wang et al (1998).…”
Section: Discussionsupporting
confidence: 90%
“…Kupffer cells are specialized tissue macrophages that represent 15% of total liver cells and almost 80e90% of all tissue macrophages in the body [2]. Macrophages are key regulators of inflammatory response during infection and the major source of inflammatory cytokines such as interleukin (IL)-6 driving acute phase protein production in hepatocytes [3,4]. However, macrophages as well as hepatic stellate cells (HSCs) also mediate tissue regeneration in response to druginduced liver damage [5], regulate the complex balance of inflammation and tissue regeneration [6,7], and facilitate cellecell communication between hepatocytes and endothelial cells (ECs) [8].…”
Section: Introductionmentioning
confidence: 99%